Leg Length and Running Speed Against Squat Long Jump Ability - Ricardo Valentino Latuheru (UNIVERSITAS NEGERI MAKASSAR, 2022)
This study aims to determine the relationship between leg length and running speed on the squat style long jump ability. This research belongs to the type of descriptive research. The population of this study was all students of SD 154 Waecekke'e, Lappariaja District, Bone Regency. The Makassar Model State with a total sample of 40 female students selected by random sampling. The data analysis technique used is correlation and regression analysis technique using the SPSS version 15.00 system at a significant level of 95% or 0.05. Starting from the results of data analysis, this study concludes that: (1) There is a significant relationship between leg length and squat style long jump ability in elementary school students 154 Waecekke'e, Lappariaja District, Bone Regency, it is proven that the value of ro = -0.845 (P < = 0.05); (2) There is a significant relationship between running speed and long jump squatting ability in SD 154 Waecekke'e Students, Lappariaja District, Bone Regency, it is proven that the value of ro = 0.771 (P < = 0.05); and, (3) There is a significant relationship between leg length and running speed on the long jump ability of the squat style at SD 154 Waecekke'e Students, Lappariaja District, Bone Regency, it is proven that the value of Ro = 0.847 (P < = 0.05).